Carbon fiber reinforced metal matrix composites: Fabrication processes and properties - Shirvanimoghaddam, Kamyar; Hamim, Salah U.; Karbalaei Akbari, Mohammad; Fakhrhoseini, Seyed Mousa; Khayyam, Hamid; Pakseresht, Amir Hossein; Ghasali, Ehsan; Zabet, Mahla; Munir, Khurram Shahzad; Jia, Shian; Davim, J. Paulo; Naebe, Minoo (Composites. Part A, Applied science and manufacturing, 2017)
This paper reviews the research and development works conducted over the past few decades on carbon fiber reinforced metal matrix composites (CFR-MMC). The structure and composition of carbon fiber and its bonding to metal matrix have an impact on the properties of the resulting CFR-MMC remarkably. The research efforts on process optimization and utilizing of carbon fibers are discussed in this review. The effect of carbon fiber on structural, physical and mechanical properties of metal matrix composite are studied as well. This review also provide an overview of the research to date on various fabrication methods that is used for production of CFR-MMC.